2009
DOI: 10.1021/ma900375g
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition Behavior of Single-Walled Carbon Nanotube−Polystyrene Composites

Abstract: A variety of measurements using a differential scanning calorimeter were used to probe how single-walled carbon nanotubes (SWCNTs) affect polymer dynamics associated with the glass transition. Tubes were dispersed in N,N-dimethylformamide containing dissolved polystyrene, and precipitation was quickly forced by the addition to large amounts of water. The percolation threshold was found to be less than 0.5 wt %, indicating good dispersion of the tubes. The glass transition temperature (T g ) increased at low na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 48 publications
3
45
0
Order By: Relevance
“…Even the fully-loaded sample had a T g that was less than the T g of the polymer. 96 This reduction is in direct contrast to normally dispersed polystyrene which has universally always caused an increase 49,71,97,98 (or no change in one case 49 ) in the glass transition temperature with added nanotubes. The difference is likely caused by wetting differences the infusion process is done at atmospheric pressure, while melt mixing is not; and in solvent-mixing processes the solvent plays a significant role in promoting wetting of the nanotubes by the polymer.…”
Section: Dynamics: Glass Transition and Diffusion Coefficientmentioning
confidence: 92%
“…Even the fully-loaded sample had a T g that was less than the T g of the polymer. 96 This reduction is in direct contrast to normally dispersed polystyrene which has universally always caused an increase 49,71,97,98 (or no change in one case 49 ) in the glass transition temperature with added nanotubes. The difference is likely caused by wetting differences the infusion process is done at atmospheric pressure, while melt mixing is not; and in solvent-mixing processes the solvent plays a significant role in promoting wetting of the nanotubes by the polymer.…”
Section: Dynamics: Glass Transition and Diffusion Coefficientmentioning
confidence: 92%
“…When CNTs are added to a polymer, T g typically increases a few degrees [30,31] but may also increase a few tenth of degrees [32]. Because of its nano- After HP&HT treatment at 1 GPa and 530 K (see experimental), the T g features of the Pcomposite and nylon-6 vanished.…”
Section: Glass Transition Behavior Of Nylon-6 and Mwcnt/nylon-6 Compomentioning
confidence: 98%
“…On the other hand, some results indicate that the addition of carbon nanotubes may deteriorate thermal stability of the epoxy matrix [5,6]. It has been also reported that modification with nanotubes changes glass transition temperature, T g [7], which in the case of the CNTs functionalised with amino groups considerably increases [8]. In this context, the aim of this work was to investigate the thermal properties of epoxy-nanotube composites with CNTs of different lengths and subjected to different surface functionalization.…”
Section: Introductionmentioning
confidence: 99%